Training of University Students of Engineering in the Use of Information - Neelameghan, A. (Journal of Information and Knowledge, 1978)
Discusses the benefits of training in information use for engineering. Presents objective, orientation, content, facilities needed, and policy for an education programme for engineering information users. Suggests a programme of action for implementing the same.